STUDENTS’ PERCEPTION ON THE USE OF PUZZLE IN TEACHING VOCABULARY MASTERY - Ratika, Andri; Isma, Adi; Nawir, Muhammad Syahruddin (English Language, Linguistics, and Culture International Journal, 2021)
This study aims to determine the students’ vocabulary mastery at second- grade students’ of SMPN 1 MAJENE, and to know students' perception on the use of puzzle in teaching vocabulary mastery. Data collection was carried out in December 2020 from 17 students of class VIII SMPN 1 Majene. This research used qualitative research, and the instruments were vocabulary test and interview. This research showed that the mean score of the vocabulary test was78 (Good) which means the students had sufficiently mastered vocabulary and could understand the vocabulary itself. The result of the interview indicated that most of the students gave positive perception on the use of puzzle, they stated that the puzzle was very good because it could increase vocabulary mastery train memory of the students, they also prefer group study because learning becomes more fun and interesting and they can ask each other what they don't know. The use of Puzzles can also increase students’ word writing, and play an active role in learning. In other words, puzzles are very helpful in learning English and make it easier for students to learn English.